2016
DOI: 10.18632/oncotarget.10426
|View full text |Cite
|
Sign up to set email alerts
|

Non-myogenic tumors display altered expression of dystrophin (DMD) and a high frequency of genetic alterations

Abstract: DMD gene mutations have been associated with the development of Dystrophinopathies. Interestingly, it has been recently reported that DMD is involved in the development and progression of myogenic tumors, assigning DMD a tumor suppressor activity in these types of cancer. However, there are only few reports that analyze DMD in non-myogenic tumors. Our study was designed to examine DMD expression and genetic alterations in non-myogenic tumors using public repositories. We also evaluated the overall survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 35 publications
6
37
0
Order By: Relevance
“…In this complex, dystroglycan binds to dystrophin in cytoskeleton and acts as a bond between cytoskeleton and extracellular matrix. In a study done on 16 types of tumor tissues, all non‐myogenic (27 paired comparison groups, including 1765 human cases) the gene expression of DMD was downregulated in 15 out of 27 (56%) of paired groups . Except for downregulation of dystrophin, dystroglycan also has showed downregulation in cancer previously.…”
Section: Resultsmentioning
confidence: 99%
“…In this complex, dystroglycan binds to dystrophin in cytoskeleton and acts as a bond between cytoskeleton and extracellular matrix. In a study done on 16 types of tumor tissues, all non‐myogenic (27 paired comparison groups, including 1765 human cases) the gene expression of DMD was downregulated in 15 out of 27 (56%) of paired groups . Except for downregulation of dystrophin, dystroglycan also has showed downregulation in cancer previously.…”
Section: Resultsmentioning
confidence: 99%
“…The tumours expressed lower levels of lamin B1 (a Dp71-binding partner), matrix metalloproteinase 2 (MMP-2) and B cell lymphoma 2 (Bcl-2) [24], which the authors linked to the reduced malignancy in this model. Subsequently, Luce et al reported significantly reduced DMD expression in lung adenocarcinoma and non-small cell lung carcinoma tissues vs. normal lung tissues using data obtained from the GEO repository with a probe set that detects all DMD transcripts [43]. Given the findings of Tan et al and the evidence from other tumours discussed in this review, it is possible that the reduced expression observed by Luce et al relates to reduced Dp427 expression, but further study is needed to confirm this hypothesis.…”
Section: Lung Adenocarcinomasmentioning
confidence: 99%
“…A recently published pan-cancer molecular study of gynecologic and breast cancers revealed that one of the genes displaying significant copy number loss when comparing pan-gynecologic to non-gynecologic is DMD 56 . Another study using data from cBioPortal, which collates next generation sequencing data from The Cancer Genome Atlas (TCGA) and the International Cancer Genome Consortium (ICGC), discovered a median mutation frequency of almost 4% in DMD in sporadic breast cancers 54 . This frequency is identical to that of more well know tumor suppressor genes in breast cancer, PTEN and ARID1A.…”
Section: Somatic Mutationsmentioning
confidence: 99%